Long Range Medical Follow-up and Updating of Computerized Records - Martin, J. M.; Pointel, J. P.; Martin, J.; Debry, G. (Methods of Information in Medicine, 1980)
In order to follow the clinical course of patients with chronic diseases, it is necessary to have a system for updating their computerized record.To achieve this objective, it is necessary to minimize the length of time devoted to information collecting and to feed the data into the computer in a manner which satisfies two essential criteria:— easy filing process,— easy access to the data for searches.In this article we will consider five aspects of the updating process of a computerized record : a file of records, any record, any elementary item, the lexicon of notions, the results of questioning before and after updating.With such a tool in hand, one can perform longitudinal studies using the data contained in the records. The approach of the authors is not only a formal one. They set up some basic formal principles from an existing experience of processing the data of several thousands of patients with diabetes and give a condensed description of the existing system.